The design of apparatus for measuring ocean wave parameters : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Information Engineering at Massey University - van der Hulst, Frank John (Massey University, 2003)
This document describes the design of a low-cost apparatus for the measurement of ocean wave parameters. The design is implemented using magnetometers to measure attitude of a free-floating buoy, and accelerometers to measure motion of the buoy, and a microprocessor to analyse the data. Calibration of the sensors is described, as well as the use of digital filtering in the analysis of the signals to determine attitude and motion. Testing of the system, both on land and on water, is described, including protection of the devices from the corrosive effects of salt water.
Appendices held with print copy in Library
Keywords: Measuring instruments; Design and construction; Ocean waves -- Measurement